The First Language Interference in Producing English Consonant Sounds - Setyaningsih, Kuntum; Wijayanto, Agus; Suparno, Suparno (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
his research deals with the problemsencountered by the students whose first language isSundanese language in learning English as a ForeignLanguage. The focus of this study is to examine the errorsmade by the students who have a Sundanese culturalbackground in producing consonant sounds. The studyused descriptive qualitative research. This study involvedthe first-grade students of Vocational High School. Thedata were collected through observations and recordings.The recording of the students' English pronunciation wastranscribed phonetically. The data were analyzed by usingcontrastive analysis techniques. The findings revealed thatSundanese students met problems in English consonantsounds while producing, [ð], [v], [f], and sounds.Sundanese students tend to shift the English consonantsounds to Sundanese sound systems when they speak. Theresults indicate that the significant differences betweenEnglish and Sundanese sound systems are the cause ofinterference. To reduce the first language interference,the teacher should learn something about phoneticfeatures of the students' first language sound systems soshe or he can predict the errors that students wouldprobably make while producing English sounds.Moreover, the students must be familiarized to speak andto listen to English in the teaching-learning process